BORBOLETAS (LEPIDOPTERA: HESPERIOIDEA E PAPILIONOIDEA) DE PORTO MAUÁ, REGIÃO DO ALTO URUGUAI, RIO GRANDE DO SUL, BRASIL - Thiele, Sabrina C.; Milcharek, Oscar; Santos, FÁBio L. d.; Kaminski, Lucas A. (Salão do Conhecimento, 2013)
Resumo